An index for defaunation - Giacomini, Henrique C.; Galetti, Mauro [UNESP] (Elsevier, 2013)
Defaunation, originally conceived as the loss of large vertebrates due to hunting or fragmentation, has been widely used in conservation studies yet the term has been arbitrarily used and poorly defined. Here we refine this term by creating a quantitative index that can be used to compare ecological communities over large zoogeographical regions. We propose a defaunation index (. D) as a weighted measure of dissimilarity between the current assemblage of a given location and a reference assemblage that represents a historical and/or unperturbed state. We analyzed the index by means of three case studies that included two empirical assessments of mammal communities in Neotropical rainforests and one hypothetical example, encompassing a variety of criteria to quantify differences in species density and importance. These cases illustrate the broad range of index applicability and show that incorporating functional differences among species, such as those based on body size, conservation status or evolutionary originality can add important information beyond simply species richness. © 2013 Elsevier Ltd.
Keywords: Atlantic Forest; Extinction; Hunting; Mammal communities; Trophic cascades; body size; habitat conservation; habitat fragmentation; hunting; mammal; mass extinction; Neotropical Region; species richness; trophic cascade; Mammalia; Vertebrata